Using Jigsaw Technique for Improving Reading Skills - Citra Ayu; Wida Rianti; Putri Asilestari (Universitas Pahlawan Tuanku Tambusai, 2021)
This research tried to find and implement actual actions to improve the quality of reading learning process for the first year students of SMAN I Kuok. The research involved the school principal, the English teacher, the researcher, and the students of SMAN I Kuok; especially the students of class X-2 of SMAN I Kuok in the academic year of 2010/2011. They consisted of 31 students, 9 males and 22 females. The students were happy and enjoyed reading using this technique. They liked to have discussions with their friends. By having discussions, the students were able to have better understanding on reading texts than before. Their cooperation was also getting better. It implies that the English teacher can use the jigsaw technique in the teaching and learning process of reading. The students should use this technique more often in order to get better understanding to comprehend the text and better cooperation with their mates.